Combination targeting of 'platelets + fibrin' enhances clot anchorage efficiency of nanoparticles for vascular drug delivery. Issue 41 (16th October 2020) - Sun, Michael; Miyazawa, Kenji; Pendekanti, Tejal; Razmi, Amaya; Firlar, Emre; Yang, Stephanie; Shokuhfar, Tolou; Li, Oliver; Li, Wei; Sen Gupta, Anirban
Abstract : Occlusive thrombosis is a central pathological event in heart attack, stroke, thromboembolism, etc . Abstract : Occlusive thrombosis is a central pathological event in heart attack, stroke, thromboembolism, etc . Therefore, pharmacological thrombolysis or anticoagulation is used for treating these diseases. However, systemic administration of such drugs causes hemorrhagic side-effects. Therefore, there is significant clinical interest in strategies for enhanced drug delivery to clots while minimizing systemic effects. One such strategy is by using drug-carrying nanoparticles surface-decorated with clot-binding ligands. Efforts in this area have focused on binding to singular targets in clots, e.g. platelets, fibrin, collagen, vWF or endothelium. Targeting vWF, collagen or endothelium maybe sub-optimal since in vivo these entities will be rapidly covered by platelets and leukocytes, and thus inaccessible for sufficient nanoparticle binding. In contrast, activated platelets and fibrin are majorly accessible for particle-binding, but their relative distribution in clots is highly heterogeneous. We hypothesized that combination-targeting of 'platelets + fibrin' will render higher clot-binding efficacy of nanoparticles, compared to targeting platelets or fibrin singularly. To test this, we utilized liposomes as model nanoparticles, decorated their surface with platelet-binding peptides (PBP) or fibrin-binding peptides (FBP) or combination (PBP + FBP) at controlled compositions, and evaluated their binding to human blood clots in vitro and in a mouse thrombosis model in vivo . In parallel, we developed a computational model of nanoparticle binding to single versus combination entities in clots. Our studies indicate that combination targeting of 'platelets + fibrin' enhances the clot-anchorage efficacy of nanoparticles while utilizing lower ligand densities, compared to targeting platelets or fibrin only. These findings provide important insights for vascular nanomedicine design.